Intelligent Modelling with Alternative Approach: Application of Advanced Artificial Intelligence into Traffic Management - Viliam Lendel; Lucia Pancikova; Lukas Falat; Dusan Marcek (Communications - Scientific letters of the University of Zilina, 2017)
The currently existing transport infrastructures are failing due to many problems. This paper deals with presenting a new approach of modelling and forecasting transport processes using artificial intelligence. Firstly, the current state of forecasting transport data is presented; the traditional as well as new artificial intelligence methods, such as artificial neural networks, are discussed and described. After that, a support vector regression prediction model is briefly presented and an empirical analysis is performed. Finally, on the basis of our experiment and performed comparative analysis we state that artificial intelligence (AI) intelligent methods have potential in the transport area as they can improve the efficiency, safety, and environmental compatibility of transport systems